Jurisdictional Control in the Sphere of Public Health Protection in the Russian Federation - Victorovich Potapenko, Sergey; Borisovich Luparev, Evgeniy (Medicine, Law & Society, 2020)
The article is devoted to the issues of mandatory judicial control over acts of subjects endowed with state powers in the field of medical activity. In particular, we consider the judicial and administrative practice of resolving administrative legal disputes in connection with instituting administrative action in the field of public health protection. The current Code of Administrative Judicial Procedure (CAJP) of the Russian Federation combines the legal procedures previously included in separate regulatory acts for judicial control in the mandatory treatment of people suffering from mental illness, the active form of tuberculosis, as well as other diseases, the list of which remains open.